The objectives for keeping the mind and its applications in artificial intelligence e-games as a model in covid-19 time - Mohd Hafiz, Yusoff@Che Abdullah; Syarilla Iryani, A. Saany; Yousef A. Baker, El-Ebiary (2020)
Artificial intelligence applications, including electronic games, have spread widely in our time among children and young people, and parents have suffered from the disruption of their children from them and the surrounding community due to sitting a lot with these applications and electronic games, especially in light of the pandemic of the Covid-19 virus, and children look at their interests, which leads to their addiction With the aim of developing their mental abilities while parents consider their interests to spend times and at the same time have many implications for achieving the goal of keeping the mind, and therefore the importance of research lies in clarifying how to preserve the mind through applications of artificial intelligence, interests and spoilers from electronic games and how to achieve them for the objective of keeping the mind, and research aims To define the objective of keeping the mind, artificial intelligence and electronic games, and to clarify its interests and spoils and how to bring interests and ward off evil through legitimate controls in order to achieve the objective of keeping the mind, the researcher used the analytical and critical inductive approach by collecting what related to the interests and spoils arising from the applications of artificial intelligence in electronic games on Achieve the intention of keeping the mind and its criticism and how to reduce spoilers by evil controls Consciousness, and the research consisted of preface and two researches, introducing the definition and legitimacy of the goal of mind keeping and artificial intelligence and electronic games, the first topic: the interests and spoils of artificial intelligence applications in electronic games to achieve the goal of keeping the mind, the second topic: legal controls for applications of artificial intelligence in electronic games to achieve a destination Preserving the mind, and a conclusion in it the most important results and recommendations, and the most important results are the importance of knowing the interests and spoils of the applications of artificial intelligence in electronic games and benefiting from these games in a way that achieves the objective of keeping the mind while working to increase its interests and ward off its corruption through the application of legal controls.